Dynamic analysis of commodity prices influence on broiler chicken prices in Malaysia - Che Rose, Farid Zamani; Sapar, Marni (Universiti Tun Hussein Onn Malaysia, 2024)
The poultry industry in Malaysia has been successful to produce more than the domestic demand over the years. Recent hike of animal feeds prices globally is an important issue in developing countries such as Malaysia that affects the cost of broilers production. This study aims to investigate the factors influencing broiler production costs in Malaysia. The factors that are included in this study are the imported ingredient for animal feeds, exchange rate and crude oil prices. This research revealed the strongest positive correlation (0.9504) between soybean meals and corn, followed by wheat and soybean meals (0.8452) in Malaysia. The structural time series model applied in this study shows that the ex-farm broiler price can be represented by a basic structural time series model. Hence, the findings from this study suggests a different approach to policy makers to ensure a low dependency on foreign resources and to protect the poultry industry in Malaysia.